Examining the dynamics between banking sector performance, environmental sustainability, and environmental technology innovation: evidence from G20 countries - Dereje Fedasa Hordofa (Cogent Business & Management, 2024)
Previous studies examined sustainability-innovation and banking-innovation linkages separately. This research addresses that gap by jointly analyzing the relationships between environmental sustainability, five banking performance metrics, and technology innovation in G20 nations from 1990 to 2022. The study constructs a banking performance index from five indicators, including return on assets, equity, deposits as a percent of GDP, risk scores, and market capitalization. A comprehensive IV-GMM approach controls for endogeneity using lagged variables as instruments in a two-step GMM model, along with the Lewbel method. Additional robustness is provided by cross-sectional, time-series FGLS regression. Results show sustainability consistently boosts innovation directly. However, examining individual banking metrics reveals that the performance index negatively correlates with innovation, excluding risk scores. Most interaction terms mirror sustainability's influence, though returns and concentrations diverge. Introducing interaction terms also inverts prior index relationships at times. Analyzing direct, interactive, and net impacts offers different views than indexing alone. The performance index positively links to net analyses versus other specifications. Overall, the findings provide empirically grounded insights into these dynamics within influential nations. Non-linearities are observed between aggregate and disaggregate banking indicators. Considering metrics from diverse analytical angles through a multidimensional lens informs optimized policy balances.
Keywords: G21; O30; Q55; Q56; 650; Banking sector performance; environmental sustainability; technological innovation; G20 countries; IV-GMM